The SH2 domain interaction landscape - Tinti, Michele (2013)
Members of the SH2 domain family modulate signal transduction by binding to short peptides containing phosphorylated tyrosines. Each domain displays a distinct preference for the sequence context of the phosphorylated residue. We have developed a new high-density peptide chip technology that allows probing the affinity of most SH2 domains for a large fraction of the entire complement of tyrosine phosphopeptides in the human proteome. Using this technique we have experimentally identified thousands of putative SH2- peptide interactions for more than 70 different SH2 domains. By integrating this rich data set with orthogonal context-specific information, we have assembled an SH2 mediated probabilistic interaction network, which we make available as a community resource in the PepSpotDB database. A new predicted dynamic interaction between the SH2 domains of the tyrosine phosphatase SHP2 and the phosphorylated tyrosine in the ERK activation loop was validated by experiments in living cells.